2018
DOI: 10.1371/journal.pone.0192279
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of a novel Group I alphabaculovirus obtained from Oxyplax ochracea

Abstract: Oxyplax ochracea (Moore) is a pest that causes severe damage to a wide range of crops, forests and fruit trees. The complete genome sequence of Oxyplax ochracea nucleopolyhedrovirus (OxocNPV) was determined using a Roche 454 pyrosequencing system. OxocNPV has a double-stranded DNA (dsDNA) genome of 113,971 bp with a G+C content of 31.1%. One hundred and twenty-four putative open reading frames (ORFs) encoding proteins of >50 amino acids in length and with minimal overlapping were predicted, which covered 92% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 65 publications
3
10
0
Order By: Relevance
“…In contrast, the gene order was significantly divergent with NeseNPV and CuniNPV (Figure 3). Consistent with previous studies [33,44,45], a conserved lepidopteran baculovirus collinear region was found in ArdiNPV, which contained 20 core genes, 5 genes conserved in lepidopteran baculovirus, and 3 other baculoviral genes (Figure 1).…”
Section: Resultssupporting
confidence: 91%
“…In contrast, the gene order was significantly divergent with NeseNPV and CuniNPV (Figure 3). Consistent with previous studies [33,44,45], a conserved lepidopteran baculovirus collinear region was found in ArdiNPV, which contained 20 core genes, 5 genes conserved in lepidopteran baculovirus, and 3 other baculoviral genes (Figure 1).…”
Section: Resultssupporting
confidence: 91%
“…They were used as query in a BLAST search against the Ref Seq protein database from all organisms deposited in GenBank ( https://blast.ncbi.nlm.nih.gov/Blast.cgi ). ORFs that encoded at least 50 amino acids and had a minimal overlap with the neighboring ORFs were selected for further characterization [ 45 ]. We set the polyhedrin start codon as the genome start position.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate the intra-populational diversity, each sequence dataset of the Chinese isolates was mapped against its respective representative genome for the individual-based analysis, and the SNPs were identified using the above method. Based on the gene-function classifications of AcMNPV and other related baculoviruses [ 45 , 52 , 53 ], all the SNPs identified in ORFs were grouped into the following six functional groups: auxiliary, replication, transcriptional, oral infection, structural and unknown function. The genetic diversity was estimated using NSSP (non-synonymous substitutions per base pair) values [ 30 ], and the result was plotted using the R statistical programming language.…”
Section: Methodsmentioning
confidence: 99%
“…Genomes of baculoviruses range from 80-180 kbp in size, encoding 90-180 genes. Approximately 37 genes are conserved across different genera of baculoviruses and have been assigned as "Core genes", involving in viral DNA replication and packaging, transcription, architecture and assembly (Herniou, Olszewski et al 2003, Herniou and Jehle 2007, van Oers and Vlak 2007, Miele, Garavaglia et al 2011, Wang, Hou et al 2018. Baculoviruses confer high degree of host specificity and insecticidal activity, thus various NPVs are being studied and developed as environmentalfriendly biological pesticides that can be effectively used for pest management in agriculture and forestry (Szewczyk, Rabalski et al 2009).…”
Section: Introductionmentioning
confidence: 99%